Investigating cognitive workload in concurrent speech-based information communication. Issue 157 (January 2022) - Fazal, Muhammad Abu ul; Ferguson, Sam; Saeed, Zafar
Highlights: Sequential information communication may be underutilising human perception capabilities and, therefore, restricting users to seek information to sub-optimal levels. Paper reports on an experiment that investigates the cognitive workload experienced by the users when listening to a variety of combinations of information types in concurrent formats. The results showed that the perceived workload index score varies in all concurrent combinations. The workload index score depends on the types and the amount of information presented to users. It is expected that the results of this experiment will contribute to helping digital content creators and designers to communicate information more efficiently to users. Abstract: Users are capable of noticing, listening, and comprehending concurrent information simultaneously, but in conventional speech-based interaction methods, systems communicate information sequentially to the users. This mismatch implies that the sequential approach may be under-utilising human perception capabilities and restricting users to seek information to sub-optimal levels. This paper reports on an experiment that investigates the cognitive workload experienced by the users when listening to a variety of combinations of information types in concurrent formats. Fifteen different combinations of concurrent information streams were investigated, and the subjective listening workload for each of the combination was measured using NASA-TLX. The results showed that the perceived workload index score varies in all concurrent combinations. The workload index score depends on the types and the amount of information presented to users. The perceived workload index score in concurrent listening remained the highest in Monolog with Interview (three concurrent talkers) combination, medium in Monolog with News Headlines (two talkers where one is intermittent) combination, and the lowest in Monolog with Music (one talker and a concurrent music stream) combination. Users descriptive feedback remained aligned with the NASA-TLX-based results. It is expected that the results of this experiment will contribute to helping digital content creators and interaction designers to communicate information more efficiently to users.